Bank Financing for Micro, Small and Medium Enterprises (Study at BPRS Saruma Sejahtera, in the Fisheries and Agriculture Sector) - Abas, Sofyan (Agrikan Jurnal Agribisnis Perikanan, 2024)
The importance of the role of lending or financing from the financial institution sector as an intermediary financing function in the MSME sector, because the contribution of the MSME sector to the regional and national economy is quite large and significant. Sharia People's Economic Bank (BPRS) Saruma Sejahtera South Halmahera has performed its function in the real sector of the economy in accordance with the mandate of law number 21 of 2008 concerning Islamic banking, namely providing financing based on contracts that may not conflict with sharia principles including customers of Micro, Small and Medium Enterprises (MSMEs) so that they can run their businesses in accordance with law number 20 of 2008 which specifically regulates MSMEs. BPRS Saruma Sejahtera as a financial intermediary between various parties in financial transactions is expected to encourage the economic activities of South Halmahera district to grow well in order to help the regional economy become more efficient and dynamic. This qualitative research is expected to determine the extent of the alignment of the Saruma Sejahtera Sharia People's Economic Bank (BPRS) to the real sector of the economy based on Micro, Small and Medium Enterprises (MSMEs) in South Halmahera Regency.The results of this study are also to determine the mechanisms and procedures for analyzing the financing of the Saruma Sejahtera Sharia People's Economic Bank to MSME actors in the agricultural and fisheries sectors in the South Halmahera region.